Ca cara no sol: memórias de desobedientes - Silva, Vinicius Alencar Da [UNIFESP] (2019)
Why do we remember? I'm here, listening to float music28, sharpening a taba, and I caught myself remembering things. I think the description of the scene will tell you possible interpretative meanings that establish alliances with my moment of remember: behind the computer, the qualification report; on the right, coffee, an ashtray - that I no longer know what I do to empty, I empty, he fills, I empty, and he I remember Rebeka and the Chains, saying, "My old lady, you don't have any a xanã?, as I heard that phrase, how many times should her ashtray suffer from the same thing? my problem - in a loneliness, ours, a cold one, I keep thinking about everybody that wrote these ethnographies, these dissertations, theses, texts, which are here, open in guides that never close, in my browser Translated with www.DeepL.com/Translator